Determination of lipid peroxidation biomarkers in vero cell line inoculated with bovine ephemeral fever virus - Oguzhan Avci*; Sibel Yavru; Irmak Dik (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the present study was to determine of lipid peroxidation biomarkers in Vero cell line inoculated with Bovine Ephemeral Fever Virus (BEFV, Genbank No: GQ229452.1). Materials and Methods: Cell supernatants were collected 4 h/day for 5 days after BEFV inoculation. Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) enzymes, glutathione (GSH) and malondialdehyde (MDA) values were analyzed from the test media by commercially available ELISA kits. In addition to this, cytopathogenic effects (CPE) of BEFV in cell culture were evaluated periodically by invert microscope. Results: In this research, CPE of BEFV was observed at 72 h post-inoculation. Maximum level of SOD was determined at 56 h, while minimum levels of CAT and GPX were determined at 8 and 104 hours, respectively. Maximum GSH levels were determined at 30, 60, 84 and 120 hours while minimum GSH concentrations were measured at 44, 92 and 112 hours. A sudden decrease of MDA level was observed in the first 8 hours occurred. In addition, CAT, MDA and SOD levels decreased before developing BEFV-caused CPE. Conclusion: It is concluded that lipid peroxidation biomarkers can be useful in the pathogenesis of BEFV. It may prove helpful in the design of future protect from decreasing of oxidative damage associated with BEFV infection.